PENGARUH PENGGUNAAN EARPLUG TERHADAP STRES KERJA BAGIAN PRODUKSI di PT TALES INTI SAWIT - Reni Aprinawaty Sirait; Plorita Situmorang (Jurnal Penelitian Kesmasy, 2020)
Work stress has become an important issue in the world of work which if allowed to occur will affect the quality of life of workers.One cause of work stress caused by noise to factory machines.The use of earplugs is expected to reduce work stress on employees exposed to noise above the NAB.This research aims to find out how much influence the use of Earplug on work stress before and after the use of Earplug in the production of PT.Tales Inti Sawit Bandar Meria Bangun Purba village.This research is a quantitative research with a Quasi experimental approach with One Group Pretest and Postest Design. The population is 46 people.The sampling technique is using purposive sampling technique with criteria: male, age 20 - 50, do not have hearing disease, work 7 hours / day according to these criteria, a sample of 30 respondents. Job stress was measured using an HRSA questionnaire with 20 questions. The average work stress before using the ear plug was 20.57 and the average after treatment in the form of earplug usage was 6.97.The average work stress before and after the use of ear plug decreased 13.6. This shows that noise affects workers psychologically which means there is a difference in the average work stress before the use of Earplug and after the use of Earplug. Based on the Wilcoxon statistical test for work stress before and after the use of ear plugs shows a significance value of p = 0,000 (p≤0.05 means that the use of ear plugs affects work stress. Employees should use ear plugs while working to avoid psychological disorders such as work stress. companies should conduct periodic monitoring and sanction for those who do not use earplugs while working